Criminal Liability for Violations of Public Employment Laws in the Republic of Kazakhstan - Baimoldina, Svetlana; Nurgalieva, Enlik; Guloglu, Yavuz; Toleukhanova, Dinara; Akchabaiev, Shynarbek (Indian Society for Education and Environment, 2015)
The specifics of the criminal liability for violations of employment rights in the Republic of Kazakhstan have been disclosed, criminal laws and other legal regulations that govern labor relations have been detailed by the authors in this paper. The authors consider the employment law to be a means of implementing the social policy in the Republic of Kazakhstan. Statistical data by the General Prosecutor Office of the Republic of Kazakhstan regarding criminal violations of public employment rights for the last five years in Kazakhstan are analyzed, crime trends associated with violation of employment laws are revealed and social and political aspects of employment guarantees are mentioned. The authors analyze scientific research done by local and foreign scientists in this area. Theoretical provisions and recommendations to improve the Kazakh employment law have been provided.
Keywords: 8. Economic growth; 10. No inequality; 16. Peace & justice